Social Recognition and Social Attraction in Group-Living Fishes - Ward, Ashley J. W.; Kent, Maud I. A.; Webster, Michael M. (Frontiers in Ecology and Evolution, 2020)
Social aggregation is a widespread and important phenomenon among fishes. Understanding the questions of why and how aggregations form and are subsequently maintained is a central goal for behavioural ecologists. Research in this field has shown that aggregations are typically structured, non-random associations. This indicates that fish are able to differentiate between potential group-mates and that this ability mediates their association preferences, and, ultimately, the composition of their groups. In this review, we examine the characteristics that influence the expression of social attraction among fishes, before going on to describe the recognition mechanisms that underpin social attraction. Finally, we highlight a number of outstanding questions in the field with a view to generating a more complete understanding of social aggregation in fishes.